A systematic approach to relief and flare systems evaluation. Issue 3 (24th July 2013) - Melhem, Georges A.
<x xml:space="preserve">Abstract</x> The process industries are primarily concerned with the reliability, availability, auditability, and maintainability of relief and flare systems data. These data are critical component of process safety information and its lifecycle must be properly managed to ensure sound process safety management and loss prevention programs. For most large facilities, the process of managing the lifecycle of relief and flare systems data are complex and fraught with challenges and risks, whether the work is performed internally or contracted out. For existing large facilities, the process of relief and flare systems evaluations require mechanical and process data collection, field verification, up to date heat and material balances, information about process safeguards, scenario identification, establishing relief requirements, identification and risk ranking of deficiencies, and managing the corrective actions process for addressing deficiencies where applicable. Reliability is influenced by many technical and human factors including the quality of data, adequacy of tools used for analysis, the qualifications of the relief systems engineers performing the scenario identification, and relief and flare systems evaluations. Availability primarily deals with how quickly can one access accurate and up to date relief and flare systems data. This is especially challenging since relief systems data are not all "structured" data and are interconnected with other engineering data systems. Auditability involves version control and the management of revisions and/or modifications of relief and flare systems that typically result from plant/process modifications, process hazard analysis, incident investigations, etc. Maintainability requires keeping the relief and flare systems data forever green and enabling efficient reviews and revisions. This article describes a systematic web‐based workflow methodology for managing the lifecycle of relief and flare systems data for a single site or at a corporate level. The workflow methodology breaks the flare and relief systems data lifecycle into discrete components and activities, with built‐in review, approval, quality management, and reporting. Built‐in business and engineering rules ensure that all activities can only progress when specific quality criteria are met. This system was developed based on our experience with the execution of many such large scale projects for refineries, chemical, and petrochemical facilities. © 2013 American Institute of Chemical Engineers Process Saf Prog 32: 230–238, 2013